Water mill canals as habitat for Margaritifera margaritifera: Stable refuge or an ecological trap? - Sousa, Ronaldo (2018)
Anthropogenic habitats may serve as a refuge for aquatic species, including freshwater mussels (Bivalvia, Unionida). Evaluating the role of anthropogenic habitats is a fundamental, but still ignored, conservation issue given the pace that humans have been converting natural ecosystems. In this study, possible differences in abundance, size and condition index of the freshwater pearl mussel Margaritifera margaritifera colonizing anthropogenic (water mill canals) and natural (Tuela River) habitats were assessed. No differences were found in the abundance of freshwater pearl mussels colonizing both habitats, but individuals present in the water mill canals have a significantly higher condition index and size. Water mill canals seem to provide stable conditions for the settlement, growth and survival of freshwater pearl mussels. However, the occurrence of an exceptional drought during the late summer of 2017 was responsible for an almost 100% mortality in one of the two water mill canals surveyed in this study. Therefore, and during extreme climatic events, these anthropogenic structures may function as an ecological trap for freshwater pearl mussels. This study can be used by managers to promote future actions that enhance freshwater pearl mussel protection and guarantee their survival, including on anthropogenic habitats.